Influence of Augmanted Reality Text Learning Media Description Of The Learning Independence of Class Students VII SMP in Central Lampung - Fauziah, SM. Wardatul; Sunarti, Iing Sunarti; Widodo, Mulyanto Widodo; Rahmayanthi, Ranni; Samhati, Siti (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This research aims to develop Augmented Reality learning media descriptive text material for class VII SMP and testing the effect of using Augmented Reality learning media for descriptive text on the learning independence of class VII SMP students in Central Lampung. The method used to develop Augmented Reality learning media is method development of Borg and Gall. The population in this study were class VII students of SMP Negeri 3 Terbanggi Besar for the 2023/2024 academic year with a sample size of 75 students. This research uses four data collection techniques, namely interviews, observation, questionnaires and tests. The results of development research show two things. First, the Augmented Reality learning media developed with the Borg and Gall concept was declared feasible by validators with an average score of 82,11%. Second, based on the feasibility test of the developed Augmented Reality learning media , an average score of 90.8 was obtained which is included in the very feasible category; The effectiveness test using N-Gain obtained a value of 0.74 which is included in the high category. This means that Augmented Reality learning media is suitable for use in learning descriptive text material and has been proven to be effective in improving students' reading comprehension abilities of descriptive text.